POLYSULFONE MEMBRANE WITH ZEOLITE FILLER FOR CO2/CH4 GAS SEPARATION: A REVIEW - Susanti, Indri (Science Education and Application Journal, 2019)
Membrane technology for gas separation applications are limited by a "trade-off" curve between permeability and selectivity. It show that permeability is high, selectivity obtained is low. This problem can be solved by preparation of Mixed-Matrix Membrane (MMMs) which can increase the value of permeability and selectivity. The MMMs with polysulfone polymers and zeolite fillers is more corresponding for gas separation. Addition of zeolite filler to polysulfone polymer in MMMs can improve the CO2 separation performance. In this review, mechanism of gas separation in MMMs was carried out in the application of CO2/CH4 gas separation. In addition, the effect of addition, size and pore of zeolite filler in MMMs for binary gas separation were also discussed in this review.